2010
DOI: 10.1111/j.1476-5381.2010.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective α7 nicotinic acetylcholine receptor agonists worsen disease in experimental colitis

Abstract: Background and purpose:In various models vagus nerve activation has been shown to ameliorate intestinal inflammation, via nicotinic acetylcholine receptors (nAChRs) expressed on immune cells. As the a7 nAChR has been put forward to mediate this effect, we studied the effect of nicotine and two selective a7 nAChR agonists (AR-R17779, (-)-spiro[1-azabicyclo[2.2.2] octane-3,5′-oxazolidin-2′-one and GSK1345038A) on disease severity in two mouse models of experimental colitis. Experimental approach: Colitis was ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 49 publications
2
72
2
1
Order By: Relevance
“…Similarly, impaired survival was also observed after nicotine treatment in septic peritonitis induced by intraperitoneal injection of E coli or fecal contamination. 60 61 Also in a model of colitis, selective α7nAChR agonists were reported to worsen disease, 62 again illustrating that dampening cytokine production is not always beneficial to the host, especially in infectious conditions.…”
Section: Clinical Significance Of the Cholinergic Anti-inflammatory Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, impaired survival was also observed after nicotine treatment in septic peritonitis induced by intraperitoneal injection of E coli or fecal contamination. 60 61 Also in a model of colitis, selective α7nAChR agonists were reported to worsen disease, 62 again illustrating that dampening cytokine production is not always beneficial to the host, especially in infectious conditions.…”
Section: Clinical Significance Of the Cholinergic Anti-inflammatory Pmentioning
confidence: 99%
“…Although both agonists reduced NF-κB transcriptional activity, IL-6 and TNF release by activated peritoneal macrophages, clinical parameters (body weight, colon weight and length), IL-6 and IL-17 levels were not augmented in vivo in two different colitis models; that is, DSS and TNBS-induced colitis. 62 Most likely, the protective effect of α7nAChR activation against excessive inflammation and collateral tissue damage compromises the host defence against the increased exposure to intraluminal microbiota following mucosal damage, suggesting that care should be taken when using these compounds in patients with IBD.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…However, chronic i.p. injection of nicotine (0.25 and 2.50 mmol/kg) in DSS-induced colitis in mice failed to decrease clinical signs of inflammation, colonic TNF levels, and histologic features of the disease (Snoek et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the secretion of ACh was reduced and colonic mucosal damage was alleviated through a 'nicotinic anti-inflammatory pathway' dependent on the α7-nicotinic acetylcholine receptor (α7nAChR) [40][41][42] . Our research showed that the discharge frequency of the vagus was decreased after chemical stimulation of the PVN, indicating that the vagus pathway played a critical role in the protective effect.…”
Section: Discussionmentioning
confidence: 99%